(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The article examined the problems associated with the reception of information in the distributed database, violations in the process of information processing in the distributed database of corporate network users, the interaction of MBBT systems, the interconnection of various data in the repository, as well as problems with B health with quality storage of data.